Visible Light-Assisted Detection of Furazolidone Using a AgFe3O4 Nanoparticle-Based Electrochemical Sensor - Nguyen, Tuan Anh (Langmuir : the ACS journal of surfaces and colloids, 2025)
This study presents a visible light-enhanced electrochemical sensor for detecting furazolidone (FZD), a widely used antibiotic, using a magnetoplasmonic AgFe3O4 nanoparticle (MagPlas NPs)-modified screen-printed electrode (SPE). Under visible light irradiation, the MagPlas-based electrochemical sensor demonstrates significantly enhanced sensitivity compared to its performance in the absence of light. This enhancement is attributed to multiple synergistic mechanisms, including photosensitization of MagPlas NPs, improved electron transfer kinetics, and increased adsorption capacity. The sensor exhibits a linear response to FZD concentrations over a wide range, achieving a low limit of detection (LOD) of 0.477 μM with visible light irradiation, demonstrating the sensor's high sensitivity. It also demonstrates good repeatability and anti-interference ability, and can be successfully applied for the determination of FZD in real milk samples. This electrochemical sensor offers a promising approach for rapid, sensitive, and reliable detection of FZD in various applications